Calibration of the superconducting gravimeter TT70 #016 at Syowa Station by parallel observation with the absolute gravimeter FG5 #203 - Iwano, Sachiko; Kimura, Isao; Fukuda, Yoichi (National Institute of Polar Research, 2003)
P(論文) For the purpose ofcalibration ofthe superconducting gravimeter model TT70 #016 at Syowa Station,Antarctica,we carried out parallel observations with the absolute gravimeter FG5 #203 from December 29, 2000 to January 25, 2001. During the FG5 measurements,the laser stability was sometimes not good and this caused irregular data.We carefully examined the relation between laser stability and gravity values,and took it into account for the removal of abnormal data.We applied linear regression to the selected SG and FG /data set,and obtained the value of -58.168 μGal/V to an accuracy of 0.10% for the scale factor of TT 70 #016.The difference of the obtained scale factor from the previous value of -57.965 μGal/V is about 0.35%. departmental bulletin paper